Fieldwork notes: an experience among the Tojolabals of Las Margaritas, Chiapas - Sánchez Franco, Irene (Revista de historia., 2024)
Field work or ethnographic exercise is an activity developed especially by anthropologists, vital for research, it is the place where the voices of two characters are put into practice: the researcher and the people who support the research process. It involves methodology, method and putting into practice the research techniques learned during the theoretical time. It implies, of course, a theoretical, epistemological, cultural, social and political position of the researcher. Some publications about the ethnographic exercise pointed out the way in which it should be done as if it were a medical prescription that must be fulfilled, others, in the Malinowski style, recounted their experiences lived in the field. Some texts have recently been published in which some researchers present field experiences and combine them with conceptual methodological use, which enriches both. This is what I work on in this text, I show my experience at the same time, the methodology, while I expose my theoretical, epistemological, social and cultural position that has implications in the ethnographic exercise.